Investigating the thermal stability of nanocrystalline aluminum-lithium alloy by combining different mechanisms: Reinforcing with graphene and alloying with Sr - Sara I. Ahmad (16936923) (2022)
Interest in nanocrystalline (nc) aluminum-lithium (Al-Li) alloys is motivated by the demand for lightweight and high-performance materials for light-weighting applications and superior fuel consumption. Nonetheless, nc metals, including Al are thermally unstable, which hinders their technological applications. In this study, we explore the effect of combining dilute amounts of strontium (1.0 at% Sr) and graphene nanoplatelets (1.0 wt% GNPs) to investigate the thermal stability of a nc Al-Li alloy. Ball milling was used to prepare four samples: Al-Li, Al-Li-Sr, Al-Li-GNPs, and Al-Li-Sr-GNPs, to systematically investigate the role of each added element. Isothermal annealing was conducted at different temperatures to investigate the thermal stability. Despite maintaining a nanometric grain size and high hardness of 70 nm and 1.1 GPa, respectively, after annealing at 773 K for 1 h, the Al-Li-Sr-GNPs sample suffered the most significant grain growth and the highest drop in hardness when compared to the Al-Li-Sr and Al-Li-GNPs samples. Microstructural investigations suggested that competing effects resulting from the spontaneous reaction of both Sr and GNPs with Al at higher temperatures resulted in a declining thermal stability efficiency. The formation and distribution of the rod-like Al4C3 phase at the grain boundaries stood in the way of proper Sr diffusion after annealing and caused the agglomeration of the Al4Sr phase. Other Information Published in: Journal of Alloys and Compounds License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jallcom.2022.165348